2023
DOI: 10.1177/02676591231157269
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of propofol-supplemented cardioplegia on biomarkers of organ injury in patients having cardiac surgery using cardiopulmonary bypass: A protocol for a randomised controlled study (ProMPT2)

Abstract: Introduction Cardiac surgery with cardiopulmonary bypass and cardioplegic arrest is known to be responsible for ischaemia and reperfusion organ injury. In a previous study, ProMPT, in patients undergoing coronary artery bypass or aortic valve surgery we demonstrated improved cardiac protection when supplementing the cardioplegia solution with propofol (6 mcg/ml). The aim of the ProMPT2 study is to determine whether higher levels of propofol added to the cardioplegia could result in increased cardiac protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Following on from the publication of the trial protocol [ 4 ], here we prospectively detail the statistical analysis plan to evaluate the ProMPT-2 trial, in advance of any outcome data analysis. This will help to reduce the risk of reporting bias and data-driven analyses.…”
Section: Discussion and Trial Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Following on from the publication of the trial protocol [ 4 ], here we prospectively detail the statistical analysis plan to evaluate the ProMPT-2 trial, in advance of any outcome data analysis. This will help to reduce the risk of reporting bias and data-driven analyses.…”
Section: Discussion and Trial Statusmentioning
confidence: 99%
“…The study population is adults undergoing first time, urgent or elective CABG surgery at a specialist UK cardiac surgery centre. Full details of the study background and design have been reported elsewhere [ 4 ]. This analysis plan was written and finalised during the 12-month follow-up period for the trial and in advance of any analysis of trial outcomes to minimise reporting bias.…”
Section: Introductionmentioning
confidence: 99%
“…The study population is adults undergoing rst time, urgent or elective CABG surgery at a specialist UK cardiac surgery centre. Full details of the study background and design have been reported elsewhere (4). This analysis plan was written and nalised during the 12-month follow-up period for the trial and in advance of any analysis of trial outcomes to minimise reporting bias.…”
Section: Introductionmentioning
confidence: 99%